2020
DOI: 10.18632/oncotarget.27694
|View full text |Cite
|
Sign up to set email alerts
|

Losartan improves the therapeutic effect of metronomic cyclophosphamide in triple negative mammary cancer models

Abstract: Metronomic chemotherapy refers to the minimum biologically effective doses of a chemotherapy agent given as a continuous regimen without extended rest periods. Drug repurposing is defined as the use of an already known drug for a new medical indication, different from the original one. In oncology the combination of these two therapeutic approaches is called "Metronomics". The aim of this work is to evaluate the therapeutic effect of cyclophosphamide in a metronomic schedule in combination with the repurposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…6d-f) [335]. This was also confirmed with different pre-clinical models [336][337][338]. The effect was attributed mainly to the high intratumoral distribution of losartan compared to other angiotensin inhibitors such as candesartan.…”
Section: Small Molecules To Target Cafsupporting
confidence: 57%
“…6d-f) [335]. This was also confirmed with different pre-clinical models [336][337][338]. The effect was attributed mainly to the high intratumoral distribution of losartan compared to other angiotensin inhibitors such as candesartan.…”
Section: Small Molecules To Target Cafsupporting
confidence: 57%
“…Generally, the AngII/AGTR1 axis is considered to promote the formation of immunosuppressive microenvironments and favor tumor growth ( 33 , 34 ). However, there are also conflicting reports suggesting potential tumor type specific differences ( 19 , 35 , 36 ). Therefore, we first screened patients with CCA from the clinical database of Department of General surgery, First Affiliated Hospital of Jinzhou Medical University, and then divided them into patients with losartan and patients without losartan combined with the treatment of adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Losartan is an FDA-approved antihypertensive agent that blocks AGTR1 (15)(16)(17). Several studies have reported the synergy of losartan with chemotherapy across numerous tumors (15,(18)(19)(20). However, no report investigated the effect of losartan on chemotherapy for patients with CCA, which is the overarching objective of this study…”
Section: Introductionmentioning
confidence: 96%
“…The heterogeneity in the vascular perfusion within the tumor arises as a result of the formation of abnormal tumor vessels, which leak and can be compressed by both cancer and stromal cells (e.g., desmoplastic tumors). The strategies to decrease tumor hypoxia through vascular normalization and normalization of cancer-associated fibroblast/extracellular matrix could improve the outcome of therapies [9][10][11][12][13]. In addition to the vascular network, other sources of heterogeneity and plasticity in the tumor microenvironment are the immune-infiltrated cells and the cancer-associated fibroblasts (CAFs) [1,14], which could have a dual role in tumor progression and metastasis [15].…”
Section: Introductionmentioning
confidence: 99%